Menumbuhkan Semangat Wirausaha Mahasiswa melalui Webinar Kewirausahaan Berkelanjutan - Yuliana FH; Dwi Hasmidyani; Ely Susanti; Muhammad Akbar Budiman (Warta LPM, 2023)
The entrepreneurial spirit is the first step that encourages individuals to start stepping into the business world. The current fact, where the number of open unemployment based on higher education levels has increased by 12.82% as of August 2021, shows that job competition is getting tougher. Thus, various efforts are needed in changing the mindset of students as job seekers to job creators. This is what prompted the Economic Education laboratory service team of FKIP Sriwijaya University to carry out online seminars/entrepreneurship webinars with the theme fostering the spirit of young entrepreneurs in the pandemic era on March 12, 2022. This activity was attended by 256 participants online. The steps for the service activities include planning, implementing and evaluating activities. The service method used is the implementation of webinars by providing explanations and material exposure, interactive discussion and question and answer with participants, and evaluation of activities by giving questionnaires. Based on the activities that have been carried out, it shows the enthusiasm of the participants in participating in this activity and getting a positive response in growing the enthusiasm and motivation of participants to start a business. This is supported by the results of the participant response questionnaire which obtained an average score of 90.91 in the aspect of growing enthusiasm and motivation for entrepreneurship. Because through this activity the participants gain insight into entrepreneurship and gain business inspiration from business actors who have tasted the sweetness of success from the business they are living. In an effort to change the mindset and create entrepreneurs among students, it is not enough just to inspire enthusiasm and motivation for entrepreneurship, further activities are needed in the form of training and assistance in realizing various business ideas that are owned, namely by providing education and capital resources that students can use. increasing entrepreneurial experience through hands-on practical activities, as well as education in terms of business development, in the form of business management, product management, and marketing techniques.